Evaluating the Evolution and Impact of Film Talent Support Programs in Chinese Film Policy (2000-2022) - Liu, Zhenyu; Indraragumhaeng, Laddawan; Wongthahan, Peerapong (Journal of Ecohumanism, 2024)
Since 2000, the Chinese film industry has transitioned to a market-oriented system, placing increased emphasis on the development of domestic film talent. The Film Industry Promotion Law, implemented in 2017, formally incorporated the "Film Talent Support Plan" into national legislation, reflecting China's commitment to cultivating film talent. Despite this, a well-defined policy framework for film talent training remains underdeveloped, and the effectiveness of current policies requires further improvement. Additionally, the collaboration between the film industry and academic institutions in talent development needs deeper exploration. This paper examines the current state of film talent training in China's film market, categorizing the types and models used. It investigates the historical role and mission of the Chinese film talent training system in the context of building China as a "film power" and promoting the healthy development of its film industry. The research objective is to analyze the characteristics of film talent support policies, evaluate their implementation and effects, and propose strategies for future improvements. Employing cultural ecology and globalization theories, this paper identifies three key characteristics of China's film talent policies: hierarchical structure, market-orientation, and collaborative frameworks. However, the impact and application of these policies need continuous enhancement. The paper concludes by recommending the establishment of an integrated mechanism linking production, education, and research, which can drive technological innovation and improve training quality, thereby ensuring the sustainable development of Chinese film talent.